Association of Veterinary Hematology and Transfusion Medicine (AVHTM) transfusion reaction small animal consensus statement (TRACS). Part 3: Diagnosis and treatment. Issue 2 (10th March 2021) - Odunayo, Adesola; Nash, Katherine J; Davidow, Elizabeth B.; Blois, Shauna L.; Goy‐Thollot, Isabelle; Harris, Lauren; Humm, Karen; Musulin, Sarah; Sharp, Claire R.; Spada, Eva; Thomason, John; Walton, Jenny; et al.
Abstract: Objective: To systematically review available evidence to develop guidelines for diagnosis and treatment of transfusion‐associated reactions in dogs and cats. Design: Standardized and systemic evaluation of the literature (identified through Medline via PubMed and Google Scholar searches) was carried out for identified transfusion reaction types in dogs and cats. The available evidence was evaluated using PICO (Population, Intervention, Comparison, Outcome) questions generated for each reaction type. The evidence was categorized by level of evidence (LOE) and quality (Good, Fair, or Poor). Guidelines, diagnostic, and treatment algorithms were generated based on the evaluation of the evidence. Consensus on the final guidelines was achieved through Delphi‐style surveys. Draft recommendations were disseminated through veterinary specialty listservs for review and comments, which were evaluated and integrated prior to final publication. Results: Medline via PubMed and Google Scholar databases were searched. There were 14 Population Intervention Comparison Outcome questions identified and corresponding worksheets were developed focusing on the diagnosis and treatment of transfusion‐associated reactions in dogs and cats. Fourteen guidelines and four algorithms were developed with a high degree of consensus. Conclusions: This systematic evidence evaluation process yielded recommended diagnostic and treatment algorithms for use in practice. However, significant knowledge gaps were identified, demonstrating the need for additional research in veterinary transfusion medicine.